Technological Pedagogical Content Knowledge On Statistics Material In Junior High School - Ichsan, Rahmi; Aswad A, Muhammad Hajarul; Raupu, Sumardin; Nasaruddin, Nasaruddin (Yayasan Insan Literasi Cendekia (INLIC) Indonesia, 2023)
Learning modules designed based on Technological Pedagogical Content Knowledge (TPACK) are very important to improve the learning experience of students. This research tries to develop a module-based TPACK for statistics in MTs Keppe, Larompong, and Luwu. This study aims to assess the feasibility and effectiveness of statistical learning modules developed based on TPACK. This research is R&D with the ADDIE models. The statistics module was developed based on the needs of junior high school students in Keppe and tested on grade VIII students. The instruments used are expert validation questionnaires practicality questionnaires to assess product feasibility, and learning outcomes tests to assess product effectiveness. The results showed that the TPACK-based statistics module can be feasible to use with validation of 85% by media experts and 87.5% by material experts, with a practicality level of 91%. This module is also effective in improving student learning outcomes with a percentage of 89.5%.